2011
DOI: 10.1007/s11832-011-0337-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of local anaesthetic on post-operative pain with wound instillation via a catheter for paediatric orthopaedic extremity surgery

Abstract: Purpose We aimed to investigate the effects on postoperative pain of local anaesthetic administration via a catheter placed into the operation site in patients who were undergoing upper and lower extremity paediatric orthopaedic surgery. Methods In this randomised, double-blind and placebo study, 40 ASA I-II patients aged between 1 and 12 years were randomly allocated into two groups: study group (Group S: 0.2 ml/kg, 0.5% bupivacaine, n = 20) and control group (Group C: 0.2 ml/kg, serum physiologic, n = 20). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…An adult meta‐analysis has found that the use of wound catheter techniques is surprisingly effective following thoracic and abdominal procedures and successful use of wound catheter techniques has also recently been reported in children following sternotomy, iliac bone grafting, and minor–moderate abdominal surgery .…”
Section: Introductionmentioning
confidence: 99%
“…An adult meta‐analysis has found that the use of wound catheter techniques is surprisingly effective following thoracic and abdominal procedures and successful use of wound catheter techniques has also recently been reported in children following sternotomy, iliac bone grafting, and minor–moderate abdominal surgery .…”
Section: Introductionmentioning
confidence: 99%
“…Bupivacaine administered locally provided prolonged desensitization of the damaged tissues, thus preventing local ectopic activity of primary afferents in the immediate post-operative period. In human, pediatric orthopaedic surgery, prolonged bupivacaine instillation via wound catheter in the postoperative period led to lower pain scores and less required additional opioids [25]. Until the day of discharge, the calf showed no signs of pain in the normal limb with exception of the wound area itself which was mildly sensitive to palpation once local anaesthetics were discontinued.…”
Section: Discussionmentioning
confidence: 99%
“…Catheters were inserted for thoracic, general and orthopaedic surgical procedures. It has been shown in the literature that catheters inserted for these indications have a positive impact on post operative pain scores [1][2][3][4] . Wound catheters remained in situ for 2.8 days on average.…”
Section: Discussionmentioning
confidence: 99%